Sleep quality and its correlates among undergraduate students of a medical school in North Karnataka, India - Kanyadi, Suhasini R.; Javali, Shivalingappa B.; Gadi, Nabeel Ahmed (International Journal Of Community Medicine And Public Health, 2024)
Background: Poor sleep quality is a global health concern and is fast becoming one of the silent epidemics. Sleep quality among medical students is of particular interest as they are considered high risk groups for developing sleep related issues because of their demanding schedules. This study aims to estimate the magnitude of poor sleep and its correlates among undergraduate medical students of a medical school in Belgaum, India. Methods: An institutional based descriptive cross-sectional study was conducted among 293 undergraduate medical students using a self-administered questionnaire. Sleep quality was assessed using Pittsburgh sleep quality index (PSQI). The potential determinants of quality of sleep were identified using logistic regression. A p<0.05 was considered statistically significant and adjusted odds ratio with 95%CI was used to present the strength of association. Results: The prevalence of poor sleep quality among medical students was 69.3%. Factors like gender, female students (AOR=2.381, 95%CI=1.359-4.172), being overweight or obese (AOR=2.499, 95%CI=1.297-4.817) were associated with poor sleep quality. Students with good sleep hygiene (AOR=0.415, 95%CI=0.231-0.745) and who did not use technology during bedtime (AOR=0.38, 95%CI=0.168-0.878) were less likely of having poor sleep quality at p<0.05. Conclusions: Prevalence of poor sleep quality among substantial proportion of medical students in the current study is alarming. The already existing personal and professional development programme committee can conduct routine screening to assess sleep quality among students and focus on programmes to improve their sleep hygiene.